Use of Public Consultation in the Nam Theun 2 Hydroelectric Project - McPhail, Kathryn (World Bank, Washington, DC, 2012)
The purpose of this note is to describe the public consultation program to date for the Nam Theun 2 (NT2) hydroelectric project and share lessons learned regarding the process and methodologies that were used. The Lao PDR is a large, sparsely populated country with rugged terrain, limited infrastructure, and a weak manufacturing base. Poverty is widespread with nearly 50 percent of the population living below the poverty line. The options available to provide substantial export earnings to help fuel long-term economic growth are limited to the export of natural resources - particularly hydroelectricity and tropical hardwoods. The objectives of public consultation in NT2 are to ensure that stakeholders are identified, key social and environmental impacts are established, and a process of stakeholder consultation and involvement in project design and implementation is put in place. The added transparency, resulting from the process of public consultation, is expected to help meet important social and environmental quality assurance objectives, which should reduce costs.